Study of the deformation process of various types of thermal insulation materials under the influence of low temperatures and moisture - E. N. Neverov; I. A. Korotkiy; P. S. Korotkih; A. N. Rasshchepkin; S. A. Samar (Vestnik MGSU)
Introduction. Refrigerating machines are used in many areas of industry to produce artificial cold. To maintain optimal operating temperatures, increase energy efficiency and reduce energy loss, thermal insulation is used during the operation of refrigerating machines. Thermal insulation is the structural elements of the refrigerator, which reduce the heat transfer process, and plays the role of the main thermal resistance in the structure. The main characteristics of thermal insulation materials are: heat conductivity, density, moisture absorption, hydrophobicity, frost resistance, strength and flammability. Depending on the conditions in which the refrigerator will be located, it is possible to determine which material will be preferable as thermal insulation. At the moment, there are many thermal insulation materials, which in turn puts the consumer at a dead end, because in most cases, the description of the characteristics of this material provides information only about its positive qualities. At the same time, its other features, which make its use insufficiently effective, are kept silent.Materials and methods. In this article, the analysis of different types of thermal insulation materials, which are priority in the design of cold storage chambers, is carried out. In order to understand which material has the characteristics we need, it is necessary to recreate the conditions under which this material will be used. To do this, several basic laboratory influences are used to create unfavorable conditions for materials.Results. As a result of these interactions, tests were performed on materials that demonstrated the strengths and weaknesses of materials under different physical conditions.Conclusions. Based on the above results, it will become clear which materials are priority as thermal insulation of the refrigerator, and which need additional processing.